Determinação de fármacos diuréticos em associação por cromatografia em camada delgada e espectrofotometria - Valladão, Dênia Mendes de Sousa; Ionashiro, Massao [UNESP]; Netto, José Zuanon (FapUNIFESP (SciELO), 2008)
A rapid, sensitive and reliable thin-layer chromatography/spectrophotometry screening procedure was developed for quantitative determination of diuretics associated in pharmaceutical dosage forms. The chromatographic method employed microcrystalline cellulose and butanol : acetic acid : water (4:1:1) or amilic alcohol : ammonium hydroxide 25% (9:1) as mobile phases and detection by U.V. light. The drugs were extracted using a simple procedure and were quantified by U.V. spectrophotometry. Results varied from 97.5 to 102.5% and are similar to those obtained by conventional methods. This method of quantification of diuretics is promising for quality control of drugs.
Determination of diuretic drugs by thin layer chromatography and spectrophotometry
Keywords: Diuretics; Quality control; Thin layer chromatography